Construction and validation of a Success in Life Scale for adults - Rivera-García, Jorge Luis (2022)
Qualitative research on success in life suggests that this construct is explained by a five-dimensional model: personal growth, social recognition, social goals, happiness, and interpersonal relationships. However, this model has not been evaluated from the point of view of other paradigms to verify its validity. This investigation aimed to test the proposed model of success in life by validating a scale. The first version of the Success in Life Scale, consisting of 72 items, was applied online to 712 volunteers living in the metropolitan area of the Mexico valley. An exploratory factor analysis (EFA) allowed us to obtain a final scale of 43 items distributed in six factors that explain 64.71 % of the variance. A confirmatory factorial analysis (CFA) validated this structure. Internal consistency analysis of the scale showed α = .95. So, we conclude that success in life is explained by factors such as personal improvement, being valued by others, moving away from the social success goals, being happy, making mistakes in achieving success, and detachment from the family.